+0  
 
0
94
1
avatar

Let v1 = <5, -1> and v2 = <-4, 2>.

Compute v1 + v2, v1v2, and v2v1.

v1 + v2 =

 

v1v2 =

 

v2v1 =

 May 19, 2020
 #1
avatar+25543 
+2

Let

\(\mathbf{v}_1 = < 5, -1 >\) and \(\mathbf{v}_2 = < -4, 2 >\).
Compute \(\mathbf{v}_1 + \mathbf{v}_2\), \(\mathbf{v}_1 – \mathbf{v}_2\), and \(\mathbf{v}_2 – \mathbf{v}_1\).
\(\mathbf{v}_1 + \mathbf{v}_2 =\)
\(\mathbf{v}_1 – \mathbf{v}_2=\)
\(\mathbf{v}_2 – \mathbf{v}_1 =\)

 

\(\begin{array}{|rcll|} \hline \mathbf{v}_1 + \mathbf{v}_2 &=& < 5, -1 > + < -4, 2 > \\ \mathbf{v}_1 + \mathbf{v}_2 &=& < 5-4, -1+2 > \\ \mathbf{v}_1 + \mathbf{v}_2 &=& < 1, 1 > \\ \\ \mathbf{v}_1 – \mathbf{v}_2 &=& < 5, -1 > - < -4, 2 > \\ \mathbf{v}_1 – \mathbf{v}_2 &=& < 5+4,-1 -2 > \\ \mathbf{v}_1 – \mathbf{v}_2 &=& < 9, -3 > \\ \\ \mathbf{v}_2 – \mathbf{v}_1 &=& < -4, 2 >- < 5, -1 > \\ \mathbf{v}_2 – \mathbf{v}_1 &=& < -4-5, 2+1 > \\ \mathbf{v}_2 – \mathbf{v}_1 &=& < -9, 3 > \\ \hline \end{array} \)

 

laugh

 May 19, 2020
edited by heureka  May 19, 2020

56 Online Users